The Role of WALHI in Advocating for Communities Affected by the Food Estate Policy during the Joko Widodo Administration (Case Study in Gunung Mas Regency, Central Kalimantan) - Naufal Hakim, Muhammad Raihan; Ilmar, Anwar (ARISTO, 2025)
This research aims to explain the role of WALHI in advocating for communities affected by the food estate policy in Gunung Mas Regency, Central Kalimantan during the Joko Widodo administration. This research uses qualitative research with descriptive-analytical method. The data collection methods used were interviews and literature studies. The researcher interviewed several WALHI members who participated in advocating related to the food estate project to the community. The researcher also conducted a literature study related to the conceptual framework of food estate, policy impact, and the main theory, namely organic intellectualism from Antonio Gramsci. The results showed that there is a paradigm problem in the food estate policy. The food estate project in Gunung Mas Regency has an impact on the rights of local communities in managing land, forest areas, local food, and traditional agricultural systems of local communities. WALHI as the largest environmental movement organisation in Indonesia realised that the food estate project actually did not care about the principle of food sovereignty centred on the independence of local communities and the creation of an environmentally friendly agricultural system. WALHI then began its role as an organic intellectual that promotes and inspires the knowledge of local communities so that they can voice their bad experiences with food estate projects.